A Case of Fatal Pulmonary Hypoplasia with Congenital Diaphragmatic Hernia, Thoracic Myelomeningocele, and Thoracic Dysplasia - Ito, Ai; Fujinaga, Hideshi; Matsui, Sachiko; Tago, Kumiko; Iwasaki, Yuka; Fujino, Shuhei; Nagasawa, Junko; Amari, Shoichiro; Kaneshige, Masao; Wada, Yuka; Takahashi, Shigehiro; Tsukamoto, Keiko; Miyazaki, Osamu; Yoshioka, Takako; Ishiguro, Akira; Ito, Yushi (American Journal of Perinatology Reports, 2017)
Background Congenital diaphragmatic hernia (CDH) is fatal in severe cases of pulmonary hypoplasia. We experienced a fatal case of pulmonary hypoplasia due to CDH, thoracic myelomeningocele (MMC), and thoracic dysplasia. This constellation of anomalies has not been previously reported.Case Report A male infant with a prenatal diagnosis of thoracic MMC with severe hydrocephalus and scoliosis was born at 36 weeks of gestation. CDH was found after birth and the patient died of respiratory failure due to pulmonary hypoplasia and persistent pulmonary hypertension of the newborn at 30 hours of age despite neonatal intensive care. An autopsy revealed a left CDH without herniation of the liver or stomach into the thoracic cavity, severe hydrocephalus, Chiari malformation type II, MMC with spina bifida from Th4 to Th12, hemivertebrae, fused ribs, deformities of the thoracic cage and legs, short trunk, and agenesis of the left kidney.Conclusion We speculate that two factors may be associated with the severe pulmonary hypoplasia: decreased thoracic space due to the herniation of visceral organs caused by CDH and thoracic dysplasia due to skeletal deformity and severe scoliosis.
Keywords: pulmonary hypoplasia; congenital diaphragmatic hernia; myelomeningocele; thoracic dysplasia; persistent pulmonary hypertension; Chiari malformation; skeletal deformity